2022
DOI: 10.1111/jocs.17149
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery bypass surgery for acute coronary syndrome: A network meta‐analysis of on‐pump cardioplegic arrest, off‐pump, and on‐pump beating heart strategies

Abstract: Background Coronary artery bypass grafting (CABG) in the setting of an acute coronary syndrome is a high‐risk procedure, and the best strategy for myocardial revascularisation remains debated. This study compares the 30‐day mortality benefit of on‐pump CABG (ONCAB), off‐pump CABG (OPCAB), and on‐pump beating heart CABG (OnBHCAB) strategies. Methods A systematic search of three electronic databases was conducted for studies comparing ONCAB with OPCAB or OnBHCAB in patients with acute coronary syndrome (ACS). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…The most recent metanalysis [1,6,7,24] showed that postoperative stroke rate is similar between patients who underwent off-pump CABG and OPBHC. These data [7] suggest that the only aortic cannulation procedure might not affect cerebral disease after surgery.…”
Section: Opbhg: Results From Secondary Research and Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent metanalysis [1,6,7,24] showed that postoperative stroke rate is similar between patients who underwent off-pump CABG and OPBHC. These data [7] suggest that the only aortic cannulation procedure might not affect cerebral disease after surgery.…”
Section: Opbhg: Results From Secondary Research and Meta-analysismentioning
confidence: 99%
“…A low level of perfusion pressure might increase the risk of hypoperfusion in the distal and subendocardial territories, as low perfusion pressure might lead to flow competition and insufficient native coronary artery blood flow. Evidence from metanalysis [1,6,7,24] suggests that a mean pressure between 70 and 80 mmHg could be an optimal level but due to few observations within the sample, more studies should be performed on this topic.…”
Section: Gaps In Evidencementioning
confidence: 99%
“…Die vergleichende Betrachtung zwischen off-und on-Pump-operierten Patienten zeigt in der überwiegenden Anzahl von Metaanalysen vergleichbare Ergebnisse auf, sodass die Auswahl des operativen Verfahren in der Koronarchirurgie überwiegend nach der Expertise und den Präferenzen der durchführenden Klinik bzw. des Operateurs durchgeführt wird [16].…”
Section: Weiterentwicklungen Und Fortschritte In Der Koronaren Bypass...unclassified
“…Surgical revascularization has recently been shown to improve long-term outcomes, although the open-chest approach is associated with increased early hazard [ 58 ]. A network meta-analysis [ 59 ] of on-pump cardioplegic arrest, off-pump, and on-pump beating heart strategies, demonstrated a superiority of the last two approaches in terms of 30-day mortality; such conclusions indicated that critically ill subjects may benefit most from avoiding further myocardial injury associated with cardiopulmonary bypass and cardioplegic arrest. After excluding re-exploration for bleeding or tamponade, patients affected by ICM undergoing CABG surgery show continuous recovery from LVD in the first post-operative year [ 22 , 60 ].…”
Section: Surgical Revascularization and Icd Implantationmentioning
confidence: 99%